Pengembangan Perangkat Pembelajaran Predict Observe Explain (POE) Berorientasi Green Chemistry Untuk Menumbuhkan Sikap Ilmiah Siswa Pada Materi Asam Basa - Muliani, Muliani; Khaeruman, Khaeruman; Dewi, Citra Ayu (Hydrogen: Jurnal Kependidikan Kimia, 2019)
One of the chemistry conceptsthat was considered difficult by students was acid-base concept. Acid-base conceptwas closely related to everyday life and includes three representations of chemical levels, namely: macroscopic level, microscopic level and symbolic level, so students experience difficulty in learning it. The development of a teaching material in the form of LKS was seen as a solution to this problem. This study aimed to develop teaching materials in the form of POE LKS oriented to green chemistry to foster students' scientific attitudes towards acid-base concepts. This studywas development research with ADDIE (Analysis, Design, Development, Implementation, and Evaluation)model design. Quantitative data from the results of feasibility validation and the results of assessment of scientific attitudes of students were analyzed by percentage formula and the results of student responses were calculated using N-gain. Qualitative data in the form of responses and suggestions for improvement from the validator. The validator's assessment of the results of the development obtained an average percentage of 83.2%, 84%, 81.6%, and 78.93%. While the responses of students were analyzed using the N-gain test obtained an average score of 0.4 with a moderate category and students' scientific attitude data obtained an average score of 61% with moderate qualifications. This showed that the LKS developed was very feasible to proceed to a broader stage and effectively improve students' scientific attitudes.